Well-defined regions of the Plasmodium falciparum reticulocyte binding protein homologue 4 mediate interaction with red blood cell membrane (2010)
Two widely studied parasite protein families are considered attractive targets for developing a fully effective antimalarial vaccine: the erythrocyte binding antigen (EBA) family defining a sialic acid-dependent invasion pathway, and reticulocyte-binding homologue (RH) proteins associated with sialic acid-independent red blood cell (RBC) invasion. In this study, the micronemal invasive PfRH4 protein was finely mapped using 20-mer-long synthetic peptides spanning the entire protein length to identify protein regions that establish high affinity interactions with human RBCs. Twenty conserved, mainly ?-helical high-activity binding peptides (HABPs) with nanomolar dissociation constants and recognizing 32, 25, 22, and 20 kDaRBCmembrane molecules in a chymotrypsin and/or trypsin-sensitive manner were identified in this protein. Anti-PfRH4 rabbit sera and PfRH4 HABPs inhibited merozoite invasion in vitro, therefore suggesting the implication of these HABPs in Plasmodium falciparum invasion and supporting their inclusion in further structural and immunological studies to design potential components of a minimal subunit-based, multiantigenic, chemically synthesized antimalarial vaccine. ©2009 American Chemical Society.